Perceived Benefits of Using Smart Lockers as Virtual Dispensing Units for Chronic Disease Medication: Healthcare Workers’ and Patients’ Perspective - Gobir, Ibrahim Bola; Niyang, Piring'ar Mercy; Adamu, Helen; Agboola, Samson; Bello, Azeez Akanbi; Havila, Nnadozie Onyinyechi; Sanni, Fatima Ohunene; Otubu, Suzzy Angmum; Bazira, Deus (British Journal of Healthcare and Medical Research, 2024)
Chronic diseases present a significant public health challenge globally, particularly in resource-limited settings like Nigeria. Effective management of chronic diseases often requires regular access to medications and adherence to treatment regimens. Smart Lockers, serving as Virtual Dispensing Units (VDU), offer a potential solution to improve medication access and adherence among individuals with chronic illnesses. However, little is known about the perceptions of healthcare workers (HCWs) and patients regarding using Smart Lockers in Nigeria. This study assessed the perceived benefits of Smart Lockers as VDU among HCWs and patients for chronic disease medications. It explored how demographic factors influence these perceptions. A descriptive cross-sectional research design was employed. Data were collected from 405 HCWs and 728 patients via a structured questionnaire. Descriptive statistics were used to analyze demographic characteristics and perceived benefits, including means, standard deviations, and percentages. Additionally, One-way Analysis of Variance (ANOVA) and t-test were conducted to explore relationships between demographics and perceptions, with significance set at p < 0.05. The results revealed that among HCWs, the perceived benefits of Smart Lockers included reduced workload (Mean = 4.40), facility decongestion (Mean = 4.50), and decreased patient waiting time (Mean = 4.57). Patients perceived benefits such as minimization of time spent waiting at healthcare facilities (Mean = 4.26) and reduced transportation costs associated with accessing care (Mean = 3.84) most positively. Significant variations in perceptions among HCWs and patients were observed based on demographic factors such as gender, age, marital status, employment status, and educational qualification. Male HCWs and patients, as well as employed patients, tended to perceive the benefits of Smart Lockers more positively compared to their female counterparts and unemployed patients, respectively (p < 0.05). Additionally, patients with higher educational qualifications expressed more favourable perceptions of Smart Locker’s benefits than those with lower educational levels (p < 0.05). Understanding these perceptions and demographic influences is crucial for effectively implementing and utilizing Smart Lockers technology in healthcare settings. Tailored interventions based on these findings can help address disparities in perceptions and enhance the acceptance and utilization of Smart Lockers for chronic disease management in Nigeria. This study provides significant perspectives into healthcare technology and chronic disease management, ultimately aiming to improve healthcare delivery and patient outcomes in Nigeria.